Negative Attitude of Public Secondary School Students towards Learning in Ife South LGA, Osun State - Ogundun, Arinade Omolara; Fadare, Abigail Oluyemisi; Ogbaini, Clement Aliu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This study examined negative attitude of public secondary school students towards education in Ife South LGA, Osun State, Nigeria. Five research questions and five research hypotheses was raised. The study adopted the descriptive research design. The population of this study consists of all public senior secondary principals, teachers, students and parents in Ife South LGA, Osun State. Two hundred and thirty (230) respondents were randomly selected as sample for this study but only One Hundred Ninety – Six (196) questionnaires were retrieved for data analysis. A structured questionnaire was constructed and administered to the respondents for data collection. The data on the bio-data of the respondents were analyzed using simple percentages, frequency distribution tables and Chi-square (X2) statistical tool at 0.05 level of significance used for analyzing the hypotheses raised. The study found no significant relationship between planning and management and negative attitudes of public secondary school students in Ife–South LGA, Osun State. However, the school environment significantly impacts students' negative attitudes. Teachers' working experience, qualifications, and physical infrastructure also play a role. A conducive learning environment should be provided by both the Federal and State Governments in Nigeria, including well-equipped laboratories, workshops, classrooms, libraries, staff offices, and classroom accommodation. In conclusion, the study highlights the importance of addressing these factors to improve students' attitudes towards education in Ife–South LGA, Osun State. The study recommends that Nigerian leaders adopt the UNESCO recommendation for funding education, taking adequate remuneration and motivation seriously for teaching staff.